Ventricular Tachycardia Ablation in the Elderly: An International Ventricular Tachycardia Center Collaborative Group Analysis. (December 2017) - Vakil, Kairav; Garcia, Santiago; Tung, Roderick; Vaseghi, Marmar; Tedrow, Usha; Della Bella, Paolo; Frankel, David S.; Vergara, Pasquale; Di Biase, Luigi; Nagashima, Koichi; Nakahara, Shiro; Tzou, Wendy S.; et al.
Abstract : Background: Successful ventricular tachycardia (VT) ablation is associated with improved survival in patients with heart failure. However, the safety and efficacy of VT ablation in the elderly, a population with higher competing nonsudden death risk and comorbidities, have not been well defined. Methods and Results: The International Ventricular Tachycardia Center Collaborative Study Group registry of 2061 patients who underwent VT ablation at 12 international centers was analyzed. Kaplan–Meier analysis was used to estimate survival of patients ≥70 years with and without VT recurrence. Of the 2049 patients who met inclusion criteria, 681 (33%) patients were ≥70 years of age (mean age, 75±4 years). Among these, 92% were men, 71% had ischemic VT, and 42% had VT storm at presentation. Mean (±SD) left ventricular ejection fraction was 30±11%. Compared with patients <70 years, patients ≥70 years had higher in-hospital (4.4% versus 2.3%; P =0.01) and 1-year mortality (15% versus 11%; P =0.002) but a similar incidence of VT recurrence at 1 year (26% versus 25%; P =0.74) and time to VT recurrence (280 versus 289 days; P =0.20). Absence of VT recurrence during follow-up was strongly associated with improved survival in patients ≥70 years. Conclusion: VT ablation in the elderly is feasible and reasonably safe with a modestly higher in-hospital and 1-year mortality, with similar rates of VT recurrence at 1 year compared with younger patients. Successful VT ablation, that is, lack of VT recurrence, is strongly associated with improved survival even in this elderly subgroup. Abstract : Supplemental Digital Content is available in the text.